Durability of left bundle branch area pacing. (26th May 2022) - Mehta, Nikhil A.; Saqi, Bilal; Sabzwari, Syed R. A.; Gupta, Rahul; Vyas, Apurva; Gordon, Jeffrey; Cossu, Sergio; Nazir, Talha; Freudenberger, Ronald; Bozorgnia, Babak
Abstract: Background: Left bundle branch area pacing (LBBAP) is a form of conduction system pacing. Long‐term data on the safety and performance of LBBAP 1 year postdevice implantation has not been well described. Methods and Results: Sixty‐five patients (49% females) who received LBBAP for bradycardia indications using the SelectSecure 3830 lead (Medtronic) were retrospectively evaluated. Clinical variables were examined. Lead parameters were obtained at implant and during regular follow‐up. Mean age of patients was 75.7 ± 10.1 years with left ventricular ejection fraction 59.8 ± 10.4%. Indications for pacing were atrioventricular block 55%, sinus node dysfunction 19%, tachy‐brady syndrome 15%, atrioventricular node ablation 8%, and bail out cardiac resynchronization therapy 3%. Mean baseline QRS measured 120 ± 38 ms, paced QRS duration was 138 ± 22ms. Paced QRS narrowed by 24 ms in those with pre‐existing left bundle branch block (BBB), increased by 1 ms in those with pre‐existing right BBB, and increased by 42 ms in those with no BBB. LBBAP threshold at implant was 0.521 ± 0.153 V at 0.4 ms, and increased to 0.654 ± 0.186 V at 3 months (+26%), 0.707 ± 0.186 V at 6 months (+36%), and 0.772 ± 0.220 V at 12 months (+48%). Patients with left BBB showed the maximum benefit with QRS narrowing 24 ms. Pacing impedance remained unchanged with no procedure‐related complications. Conclusion: LBBAP is a durable form of conduction system pacing with pacing thresholds remaining relatively stable over 12 months post device implantation. Patients with left BBB display the narrowest paced QRS. Abstract : We evaluate the performance of left bundle branch area pacing in 65 patients over 12 months. Pacing thresholds at the time of implant measured 0.521 V at 0.4 ms, and increased to 0.654 V at 3 months (+26%), 0.707 V at 6 months (+36%), and 0.772 V at 12 months (+48%). Pacing impedances remained unchanged.